Trans-Heteroleptic carboxylate-bridged paddlewheel diruthenium(ii, ii) complexes with 2, 6-bis(trifluoromethyl)benzoate ligands. Issue 17 (4th April 2016) - Sekine, Yoshihiro; Kosaka, Wataru; Kano, Hirohisa; Dou, Changxiao; Yokoyama, Taiga; Miyasaka, Hitoshi
Abstract : A series of trans -heteroleptic carboxylate-bridged paddlewheel diruthenium(ii, ii ) complexes were synthesized via the ligand-substitution reaction and valence reduction of homoleptic series [Ru2 (RCO2 )4 (THF)2 ] + using 2, 6-trifluoromethylbenzoate. Abstract : Carboxylate-ligand substitution reactions of paddlewheel-type diruthenium(ii, iii ) complexes ([RuII, III2(RCO2 )4 ] + ) with 2, 6-bis(trifluoromethyl)benzoate (2, 6-(CF3 )2 PhCO2 − ) involving a selective reduction to [RuII, II2] provide a series of trans -substituted paddlewheel-type diruthenium(ii, ii ) complexes, [RuII, II2(2, 6-(CF3 )2 PhCO2 )2 (RCO2 )2 (THF)2 ] (R = CH3, 1 ; C2 H5, 2 ; C3 H7, 3 ; C4 H9, 4 ; C(CH3 )3, 5 ; 2, 3, 5, 6-F4 Ph, 6 ). Crystal structures of1–6 were determined, and their electronic states were investigated by cyclic voltammetry, density functional theory (DFT) and magnetic measurements. This is the first example of trans -heteroleptic carboxylate-bridged [RuII, II2] complexes.